2022
DOI: 10.3390/ijms23073925
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Sericin Hydrolysates Modified by Alcalase® Suppress Melanogenesis in Human Melanin-Producing Cells via Modulating MITF

Abstract: Because available depigmenting agents exhibit short efficacy and serious side effects, sericin, a waste protein from the silk industry, was hydrolyzed using Alcalase® to evaluate its anti-melanogenic activity in human melanin-producing cells. Sericin hydrolysates consisted of sericin-related peptides in differing amounts and smaller sizes compared with unhydrolyzed sericin, as respectively demonstrated by peptidomic and SDS-PAGE analysis. The lower half-maximum inhibitory concentration (9.05 ± 0.66 mg/mL) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Although UVR is one of the major melanoma risk factors it is also essential for initiating vitamin D synthesis, while active forms of vitamin D also have photoprotective properties [266][267][268]. The topical treatment of large or non-resectable melanoma lesions including lentigo maligna using a combination of melatonin and sericin also shows that mitochondrial and antioxidant protection activity may lead to the development of a valuable additional strategy targeting melanoma, regarding the antibacterial properties of sericin that accelerate wound healing [269,270].…”
Section: Discussion: Melatonin/sericin Collagen Scaffolds As Possible...mentioning
confidence: 99%
“…Although UVR is one of the major melanoma risk factors it is also essential for initiating vitamin D synthesis, while active forms of vitamin D also have photoprotective properties [266][267][268]. The topical treatment of large or non-resectable melanoma lesions including lentigo maligna using a combination of melatonin and sericin also shows that mitochondrial and antioxidant protection activity may lead to the development of a valuable additional strategy targeting melanoma, regarding the antibacterial properties of sericin that accelerate wound healing [269,270].…”
Section: Discussion: Melatonin/sericin Collagen Scaffolds As Possible...mentioning
confidence: 99%
“…Although the mechanism of melanosome transferring from melanocyte to keratinocyte is still unclear, it is a quite important step to maintain and protect the healthiness of cells. Melanin deposited in the basal layer has melanogenic properties to melanocytes and inhibition on keratinocytes proliferation [ 29 , 30 ]. Meanwhile, the content of melanin in the epidermis can be decreased by excretion and reduction reactions to achieve the aim of whitening.…”
Section: Discussionmentioning
confidence: 99%
“…β -Actin was used as the internal reference in the analysis of protein expression. Samples were run as independent replicates repeated thrice for each group [ 29 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…SS is a versatile biopolymer that has been used to create biomaterials for various applications, [13] and multiple studies have shown that SS has antioxidant, anti-inflammatory, scar-preventing, and woundhealing properties. [14][15][16] Additionally, the amino acids in SS are predominantly hydrophilic, leading to a strong ability to absorb water, which can prevent water loss and promote the proliferation of collagen. [17] Silver nanoparticles (AgNPs) have been shown to exert a strong killing effect on a variety of pathogenic microorganisms, such as E. coli and S. aureus, and their use does not lead to resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Another potential additive to wound‐healing polymers is silk sericin (SS), which wraps around the core fibroin fibers that give silk its structural properties. SS is a versatile biopolymer that has been used to create biomaterials for various applications, [13] and multiple studies have shown that SS has antioxidant, anti‐inflammatory, scar‐preventing, and wound‐healing properties [14–16] . Additionally, the amino acids in SS are predominantly hydrophilic, leading to a strong ability to absorb water, which can prevent water loss and promote the proliferation of collagen [17] …”
Section: Introductionmentioning
confidence: 99%